2006
DOI: 10.1083/jcb.200601018
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial–mesenchymal transition: new insights in signaling, development, and disease

Abstract: The conversion of an epithelial cell to a mesenchymal cell is critical to metazoan embryogenesis and a defining structural feature of organ development. Current interest in this process, which is described as an epithelial–mesenchymal transition (EMT), stems from its developmental importance and its involvement in several adult pathologies. Interest and research in EMT are currently at a high level, as seen by the attendance at the recent EMT meeting in Vancouver, Canada (October 1–3, 2005). The meeting, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
1,574
1
36

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,826 publications
(1,671 citation statements)
references
References 59 publications
49
1,574
1
36
Order By: Relevance
“…CK expression in both differentiated and dedifferentiated SRCCs had also been described in previous studies [64,69]. Moreover, N-cadherin, an EMT marker with increased expression in the presence of EMT [73] was not observed in intramucosal foci of SRC [52]. In conclusion, the role of EMT in the development of aggressive and widely invasive HDGC from early and indolent microscopic foci is uncertain and further analysis of these lesions is necessary to understand the molecular events required for the progression from indolent intramucosal lesions to widely invasive carcinomas.…”
Section: Immunohistochemical Profile Of Hdgc and Its Relationship Witsupporting
confidence: 75%
“…CK expression in both differentiated and dedifferentiated SRCCs had also been described in previous studies [64,69]. Moreover, N-cadherin, an EMT marker with increased expression in the presence of EMT [73] was not observed in intramucosal foci of SRC [52]. In conclusion, the role of EMT in the development of aggressive and widely invasive HDGC from early and indolent microscopic foci is uncertain and further analysis of these lesions is necessary to understand the molecular events required for the progression from indolent intramucosal lesions to widely invasive carcinomas.…”
Section: Immunohistochemical Profile Of Hdgc and Its Relationship Witsupporting
confidence: 75%
“…In this study, we found that LINC00704 could affect epithelial mesenchymal transition (EMT) process by regulating E‐cadherin, N‐cadherin, and β‐catenin expression in thyroid cancer. EMT is a biologic process by which epithelial cells lose their polarity and gain migratory and invasive properties to transition into a mesenchymal phenotype 31. EMT has been determined to be essential for numerous developmental processes, and increasing evidence reveals that EMT also occurs in the initiation of tumor cells metastasis during cancer progression 32.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic of EMT is that cells acquire mesenchymal cell markers (eg, N‐cadherin and vimentin) and lose epithelial cell markers (eg, E‐cadherin) 5, 6. EMT occurs during the progression of tumors of various origins, including prostate, breast, hepatic, gastric, pancreatic, and colorectal cancer 7, 8, 9, 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%